The Effectiveness of Integrating Complementary Therapy with Modern Wound Dressings on the Healing of Diabetic Wounds - Wiwiek Hidayati Jaya; Ambo Anto; Rijalul Fikri; Rismanudin Rismanudin; Sahari Bulan (Universitas Pahlawan Tuanku Tambusai, 2026)
Abstract Delayed healing, severe infections, and amputations are real threats resulting from chronic complications of diabetic wounds in people with diabetes mellitus. To address this, the integration of complementary care and modern wound dressing technology is now being considered as a promising strategy. This study aims to examine the impact of this integration on accelerating wound healing. Using a quantitative quasi-experimental design, participants were grouped into intervention and control groups through purposive sampling. Patients in the intervention group were treated using a combination of complementary therapy and modern wound dressings, while the control group received only standard modern wound care. Healing rates were measured using standardized assessment tools before and after the intervention. The data showed a significant improvement in wound condition in the intervention group compared to the control group (p < 0.05). This success was demonstrated by a reduction in wound area, better granulation tissue formation, minimal exudate, and faster epithelialization. This study proves that combining complementary therapy with modern wound dressings yields far more effective results in healing diabetic wounds than modern wound dressing methods alone.